Pyloric botulinum toxin for diabetic gastroparesis: a case of sustained glycaemic improvement - Luke Bugeja; Lianne Camilleri; John Schembri (European Journal of Case Reports in Internal Medicine)
Introduction: Diabetic gastroparesis is a gastrointestinal motility disorder defined as a delay in gastric emptying time without any mechanical obstruction. This affects about 40% of patients with type 1 diabetes and up to 30% of patients with type 2 diabetes, especially those with long-standing disease, and arises from dysfunction of the autonomic and enteric nervous systems. Unfortunately, it can cause great difficulty in controlling post-meal glucose excursions because food absorption can become unpredictable in this group of patients. Gastroparesis is therefore linked with fluctuations in glycaemic control due to variable nutrient absorption. This may worsen the extent of gastroparesis, making glucose control even more difficult. Treatment with botulinum toxin injections has been described in clinical trials with doubtful efficacy to abating symptoms associated with gastroparesis. Case presentation: We report a case of how pyloric botulinum toxin injections significantly improved a patient’s type 1 diabetic control and gastrointestinal symptoms associated with gastroparesis and is still maintaining improved glucose levels six months after her procedure. Although current data and case studies highlight a potential role for pyloric botulinum toxin injections, no association was found between pyloric botulinum toxin injections and blood glucose control in type 1 diabetics. Conclusion: This article examines a potential promising association between botulinum toxin injection in the pylorus and enhanced diabetic control in type 1 diabetics.